Solidification microstructure variations in additively manufactured Ti-6Al-4V using laser powder bed fusion. (1st July 2023) - Yang, Lu; Ramachandran, Saranarayanan; Bagasol, Axieh; Guan, Qiyu; Wang, Weiguang; Browne, David J.; Dowling, Denis; Mirihanage, Wajira
Abstract: Laser powder bed fusion (LPBF) offers unique opportunities to produce metallic components without conventional design and manufacturing constraints. During additive manufacturing process, titanium alloys like Ti-6Al-4V undergo solid-state transformation that conceals initial solidification microstructure from room-temperature observations. Revealing the as-solidified microstructure can be critical to understanding the early stages of solidification. Using orientation relationships between parent (α) and child (β) phases, the as-solidified microstructures across the LPBF build volume has been reconstructed. Based on the as-solidified parent phase information, variations of the thermal and solidification conditions that occur during the LPBF of Ti-6Al-4V are revealed. The results show that how high cooling rates in the initially solidified lower layers contributed to orientation distribution during parent phase solidification, compared to upper layers in the build volume. Furthermore, the approach demonstrates the potential to further explore solidification microstructure and defect formation in titanium alloys during additive manufacturing. Graphical Abstract: Image, graphical abstract